The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1471-2164-13-9
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock-regulated gene expression patterns associated with fire blight resistance in apple

Abstract: BackgroundDesirable apple varieties are clonally propagated by grafting vegetative scions onto rootstocks. Rootstocks influence many phenotypic traits of the scion, including resistance to pathogens such as Erwinia amylovora, which causes fire blight, the most serious bacterial disease of apple. The purpose of the present study was to quantify rootstock-mediated differences in scion fire blight susceptibility and to identify transcripts in the scion whose expression levels correlated with this response.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 36 publications
1
67
0
Order By: Relevance
“…In addition to the abovementioned miRNAs, we also examined miRNAs targeting transcripts previously identified by us as up-or downregulated in FB-resistant trees (Jensen et al 2012). We identified three candidates, which might be targeted by miRNAs expressed in analyzed trees: NHX1, nodulin, and dinelactone hydrolase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the abovementioned miRNAs, we also examined miRNAs targeting transcripts previously identified by us as up-or downregulated in FB-resistant trees (Jensen et al 2012). We identified three candidates, which might be targeted by miRNAs expressed in analyzed trees: NHX1, nodulin, and dinelactone hydrolase.…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier studies, we identified 690 genes up-or downregulated in FB-resistant trees (Jensen et al 2012). This set of genes was obtained for the same scion/rootstock combinations as in this study.…”
Section: Target Predictionmentioning
confidence: 96%
See 1 more Smart Citation
“…The overall result is an organ-and developmentally specific pattern of metabolites, characteristic for each plant species. Jensen et al (2012) suggested that the expression of the phenylpropanoid pathway as a whole might be one of the many predictors of fire blight resistance. Burse et al (2004) already showed that E. amylovora has the ability to protect itself against secondary metabolites in apple because of the internal efflux pump AcrAB, indicating the possible involvement of these metabolites in plant defence.…”
Section: Secondary Metabolitesmentioning
confidence: 99%
“…In response to pathogen infection, the synthesis of defense-related phenolics such as flavonoids, phenolamines, flavonoid phytoalexins, lignin and salicylic acid (SA) is enhanced (Treutter 2001;Venisse et al 2002;Fischer et al 2007). Jensen et al (2012) suggested that the phenylpropanoid pathway mobilization and activity might be one of the hallmarks of fire blight resistance. However, it should be taken into account that although the stimulation of this pathway is a part of plant resistance response, the processes are dependent also on pathogen activity; E. amylovora belongs to the pathogens which in order to overcome plant defense can delay the expression of phenylpropanoid genes (Venisse et al 2002).…”
Section: Introductionmentioning
confidence: 99%